Socialization and Making of Landslide Disaster Warning Equipment in Gentan Village, Sukoharjo - Budi Siswanto; Aznika Putu Dhiyani; Bhisma Pandya Suryanendra; Dewi Azizah Nur Safitri; Muhammad Hafizh Rafi; Muhammad Safiq Prasetyo; Raoul Kennan; Vernanda Salsabila Zalfa; Vincensia Mutiara Rengganis; Wildan Naufal Ardhi; Yusuf Nur Wahyudi (Universitas Sahid Surakarta, 2024)
Abstract: This research aims to enhance the awareness and consciousness of the community regarding the potential disasters that may occur in Gentan Village. Various types of natural disasters frequently occur in Gentan Village, one of which is landslides. In this study, a device was created and installed in landslide-prone areas of Gentan Village. The purpose of this device is to provide notifications in the form of a siren when a landslide disaster occurs, with the hope that it will be beneficial to the surrounding community. In the implementation of this activity, Badan Penanggulangan Bencana Daerah (BPBD) participated in providing information about natural disasters and how to mitigate them. BPBD and the local community also supported and actively participated in the installation of landslide warning devices in landslide-prone areas. The impact of this activity has been able to increase the knowledge and awareness of the Gentan Village community regarding landslide disasters. The landslide warning devices are expected to be replicated and further developed to become more effective. Keywords: disaster, warning signal, technology